Diagnóstico Y Análisis De La Comercialización De Arroz Para Elaborar Una Alternativa En Mejorar La Rentabilidad De Los Productores De La Zona De Babahoyo - Suárez, Maribel Vera; Paredes, Joffre León; Mora, Rosa Guillén; Betancourt, Ricardo Chávez; Barbotó, Víctor Molina; Perez, Álvaro Pazmiño; López, Sergio Cristóbal Suárez (European Scientific Journal, ESJ, 2017)
The development of the production of arrocera in Ecuador was possible because it consolidated a complementary industrial sector. The rice industry, however, appears as a consequence and condition for the consolidation of this branch of production. The general advancement of the production process takes into account the growth of an industrial sector devoted to the decorticamiento of the gramínea. This is based on the fact that the industrialisation of the grain is a condition for the increase of consumption. In turn, one can understand the growth of the latter (especially in the sierra), if they take into account the new forms of utilisation of the rice that the processing gives place. This is a fundamental requirement for the development of the industry and, therefore, the general production. It should be emphasised that after the harvesting process, the primary production concludes with the storage of the grain in sacks or silos. The industrialisation of rice begins with the drying of the grains. Once these are completely dehydrated, it proceeded to the husked and the removal of the husk thereof. As a result of this process, you can get the brown rice which in some cases is treated with specialized polishing machines to obtain the white rice that is consumed regularly. Usually, the process of industrialization ends with the packaging of the rice for human consumption. In actuality, the rice sector faces great challenges. This is the same ones that make it essential to form rice associations for small and medium producers to handle their own industrialization process. It, however, begins with the drying of rice Peel, storage in silos, hulling and elimination of husk, polishing (white rice) and packaging, and taking care of the marketing in the domestic market, i.e. direct selling, especially in supermarkets and Points of Sale being the best option. For Producers, the commercial opening is an opportunity for rice activity.